Comparison of Ramadhan and pre-Ramadhan diabetic ketoacidosis (DKA) admission among type-II diabetic mellitus patients admitted in Hospital Sultanah Nur Zahirah Kuala Terengganu : associated factors, outcome and severity - Zakaria, Muhamad Fakruradzi (2023)
Background: Diabetic Ketoacidosis (DKA) is one of the most common life-threatening complications of diabetes mellitus. There are limited published studies on DKA among Type 2 Diabetes Mellitus (T2DM) patients during Ramadhan in Malaysia, particularly in the oast region. Therefore, this study aims to determine the associated factors for DKA admission for T2DM patients, as well as to compare the outcomes and severity of DKA admission between pre-Ramadhan and during Ramadhan. Method: This is a comparative cross-sectional study. The study population involved all DKA admissions in patients with type 2 DM before and during Ramadhan to medical ward in Hospital Sultanah Nur Zahirah, Terengganu between January 2015 to December 2019. The demographics, underlying history and clinical data for patients were retrieved from the medical records of the patients. Result: A total of 117 DKA admissions in the medical ward department of HSNZ which involved 83 admissions pre-Ramadhan, and 34 admissions during Ramadhan. Analysis showed insulin and diabetes complications were the associated factors for DKA. Besides, there were no significant differences in length of stay and mortality between Pre-Ramadhan and during Ramadhan (p>0.05), whereas the severity of DKA was significantly different between those two periods (p<0.001) Conclusion: Insulin and complications were the associated factors for DKA. The severity of DKA admission in T2DM patients was found to be severe during Ramadhan compared to non-Ramadhan. However, the outcome and factors that lead to DKA admissions was similar during Ramadhan and pre-Ramadhan.